THE BOOK SEALED WITH SEVEN SEALS (REV 5. 1): THREE REMARKABLE PATRISTIC INTERPRETATIONS - Androsova, Veronika (Sacra scripta, 2014)
This article examines various interpretations regarding the book written inside and out and sealed with seven seals (Revelation 5,1) which appears as the central symbol of the fifth chapter of the Revelation of Saint John. The figure of the book continues to be of great interest to commentators who find ever new interpretations of the passage. The author of this article has tried to collect these various interpretations and order them into three major groups. At the same time, the author was guided in her choice of these interpretations by the factor of their presence in the patristic tradition. The first group of interpretations points to the Old Testament. The meaning of the Old Testament is opened by Christ and through the figure of Christ becomes understandable. The second group of interpretations envisages the book as holding those things which pertain to the final fate of the world given over to Christ who appears as the fulfillment of God's plan of salvation and the master of destiny. In the third interpretation, the sealed book represents the divine testament which is inherited by Christ who accepts death for mankind. The author wishes to highlight a certain chain of borrowings linking the various interpretations as well as a certain planned inter-coordination of all these interpretations of the passage. The author concludes that in spite of the apparent differences between the various interpretations, they nevertheless share some common points which result from their thematic intertwining.